Web-Based Parent Training With Telephone Coaching Aimed at Treating Child Disruptive Behaviors in a Clinical Setting During the COVID-19 Pandemic: Single-Group Study With 2-Year Follow-Up - Sourander, Saana; Westerlund, Minja; Baumel, Amit; Hinkka-Yli-Salomäki, Susanna; Ristkari, Terja; Kurki, Marjo; Sourander, Andre (JMIR Publications Inc., 2025)
Background: There is a lack of studies examining the long-term outcomes of web-based parent training programs implemented in clinical settings during the COVID-19 pandemic.
Objective: The aim is to study 2-year outcomes of families with 3‐ to 8-year-old children referred from family counseling centers to the Finnish Strongest Families Smart Website (SFSW), which provides digital parent training with telephone coaching aimed at treating child disruptive behaviors.
Methods: Counseling centers in Helsinki identified fifty 3‐ to 8-year-old children with high levels of disruptive behavioral problems. Child psychopathology and functioning as well as parenting styles and parental mental health were collected from parents at baseline; posttreatment; and at 6-, 12-, and 24-month follow-ups.
Results: The SFSW program had positive long-term changes in child psychopathology and parenting skills. Improvements in child psychopathology, including Strengths and Difficulties Questionnaire total score (Cohen d=0.47; P < .001), Strengths and Difficulties Questionnaire conduct scores (Cohen d=0.65; P < .001), and Affective Reactivity Index irritability scores (Cohen d=0.52; P < .001), were maintained until the 24-month follow-up. Similarly, changes in parenting skills measured with the Parenting Scale, including overreactivity (Cohen d=0.41; P = .001) and laxness (Cohen d=0.26; P = .02), were maintained until the 24-month follow-up. However, parental hostility changes were not maintained at long-term follow-up (Cohen d=−0.04; P = .70).
Conclusions: The study shows that the SFSW parent training program can yield significant long-term benefits. Findings indicate that the benefits of the treatment may vary between different parenting styles, which is important to consider when developing more personalized parenting interventions.